Electrical resistivity imaging for aquifer mapping over Chikotra basin, Kolhapur district, Maharashtra - Gupta, Gautam; Patil, J.D.; Maiti, Saumen; Erram, Vinit C.; Pawar, N.J.; Mahajan, S.H.; Suryawanshi, R.A. (My University, 2015)
Electrical resistivity study assumes a special significance for mapping aquifers in hard rock areas. A two-dimensional (2D) resistivity survey of Chikotra basin, southern part of Kolhapur district in the Deccan Volcanic Province of Maharashtra was conducted. The aim of this work was to determine the aquifer zones of the study area using electrical resistivity imaging technique. The hydro-geological section derived from the available dug well/borehole lithology suggests that the top layer comprises red bole, laterite or black soil followed by weathered/fractured rock grading into compact basalts. The sources of groundwater appear to be available in weathered and fractured basalt trapped between weathered overburden and hard rock. Results from the 2D inverted models of resistivity variation with depth suggest the occurrence of aquifers mostly in weathered/fractured zones within the traps or beneath it. The resistivity models suggest that the northern part of the study area represents a promising aquifer zone with reasonable thickness of weathered basement. The models further indicate that there are several locations throughout the basin for possible groundwater exploration as it exhibited strong water-bearing potential in the subsurface rocks.
Keywords: Aquifers; Electrical resistivity imaging (ERI); Groundwater; Chikotra basin; Deccan volcanic province; Maharashtra; Kolhapur